The MDM2 polymorphism SNP309 is associated with clinical characteristics and outcome in diffuse large B-cell lymphoma - Hedstrom, Gustav; Thunberg, Ulf; Amini, Rose-Marie; Zainuddin, Norafiza; Enblad, Gunilla; Berglund, Mattias (John Wiley & Sons Ltd, 2014)
Introduction The murine double minute 2 (MDM2) gene encodes a regulatory protein of the p53 pathway. A single nucleotide polymorphism (T to G change) at position 309 (SNP309) in the promotor region of MDM2 affects the transcription activity of MDM2 and has been found to be a negative prognostic marker in several cancers.